Building energy conservation potentials of semi-transparent CdTe integrated photovoltaic window systems in Bangladesh context. (May 2023) - Uddin, Md Muin; Ji, Jie; Wang, Chuyao; Zhang, Chengyan
Abstract: Building integrated photovoltaic systems are getting popular worldwide due to their building energy conservation properties alongside emission-free electricity generation capabilities. BIPV is a suitable way to generate renewable energy without wasting any land or building space. Bangladesh has set a target to generate a great portion of its electricity from solar energy and has already implemented different photovoltaic applications. However, Bangladesh still has no policy and guidelines to implement BIPV technology in its different types of buildings. In this study, we investigated the energy conservation potentials of three different configurations of semi-transparent CdTe combined building integrated window systems in an office building considering Bangladesh's climate conditions. To investigate the building energy conservation potentials of BIPV window systems, an EnergyPlus-based numerical simulation model was developed and validated with outdoor experiment data. The annual energy simulation results indicate that in all climate conditions, CdTe combined BIPV windows can save ranging from around 30–61% of electricity consumption compared to conventional window systems. Besides, it generate around 270 kWh electricity and ensure indoor daylight illuminance level at 300 lux. Moreover, in all climate conditions, south-faced BIPV windows are more efficient for power generation, but east-faced windows are more efficient to reduce net electricity consumption.